Investigating the Economic Significance of Tourism Destinations: A Bibliometric Analysis of the Travel Cost Method - Arya, Muhammad Arya Padilla; Diswandi, Diswandi (Faculty of Economics and Business, University of Mataram, 2024)
This paper presents a comprehensive bibliometric analysis aimed at investigating the efficiency and trajectory of the Travel Cost Method (TCM) in tourism research. Drawing upon a systematic search of scholarly publications using electronic databases such as Web of Science, Scopus, and Google Scholar, we identified a corpus of articles focusing on TCM application, methodology, or evaluation in the context of tourism. Employing VOSviewer software, we conducted a detailed analysis of bibliometric indicators including citation counts, co-authorship networks, keyword co-occurrence, and citation bursts to elucidate patterns, trends, and influential works within the TCM literature in tourism. Our findings highlight the growing importance of TCM as a valuable tool for economic valuation, decision-making, and policy formulation in the tourism industry. The analysis revealed a diverse array of research themes spanning economic valuation, visitor demand analysis, environmental impact assessment, and sustainable tourism management. Methodological advancements, including the integration of stated preference techniques and spatial analysis methods, were identified as key drivers enhancing the accuracy and reliability of economic valuation estimates. The implications of the findings extend beyond academia to inform practice and policy in the tourism sector, offering practical insights for tourism planners, managers, and policymakers seeking to balance economic development with environmental conservation and social welfare objectives. By contributing to a deeper understanding of the role of TCM in shaping tourism research and informing sustainable tourism management practices, this study provides valuable insights for stakeholders in academia, industry, and policy-making.